Aspects of Health Reform: Contributions from the Economic Research Initiative on the Uninsured. Aspects of Health Reform: Introduction - Catherine McLaughlin; Helen Levy; Brian Quinn (SAGE Publishing, 2009)
From 2001 to 2008, the Robert Wood Johnson Foundation funded the Economic Research Initiative on the Uninsured (ERIU), housed at the University of Michigan. The goals of ERIU were to increase, diversify, and improve the quality and quantity of economics research on the uninsured, and to translate that research into the type of resources that are useful to policymakers, policy analysts, researchers, and members of the media. One of the primary objectives of ERIU was to fund research projects that explored economic issues about the uninsured in new, yet rigorous and interesting ways. ERIU began by commissioning six critical syntheses of the existing research. These syntheses were intended to inform researchers of what we know and what we don't know about the uninsured. In eight years, ERIU funded more than 50 new research projects on a variety of coverage topics aimed at addressing the gaps in knowledge highlighted in these syntheses. These projects, involving more than 100 researchers, resulted in over 70 conference and seminar presentations worldwide and approximately 40 articles published in peer-reviewed journals.